Transfer Pricing, Thin Capitalization, Financial Distress, Earning Management, dan Capital Intensity Terhadap Tax Avoidance Dimoderasi oleh Sales Growth - Mauliddini Nadhifah; Abubakar Arif (Jurnal Magister Akuntansi Trisakti, 2020)
This study aims to examine the effect of transfer pricing, thin capitalization, financial distress, earnings management, and capital intensity on tax avoidance with sales growth as moderating. This study uses a sample of manufacturing companies in the basic industrial sector and chemical goods, the consumer goods industry sector, and other goods industry sectors listed on the Indonesia Stock Exchange during the 2016-2018 period as many as 32 companies. Data collection techniques using purposive sampling method and analyze using panel data multiple regression method. The results showed that transfer pricing, financial distress, earnings management, and sales growth have a negative effect on tax avoidance. Thin capitalization has a positive effect on tax avoidance, while capital intensity has no effect on tax avoidance. Sales growth as a moderator is able to strengthen the negative influence of transfer pricing and financial distress and the positive influence of thin capitalization and capital intensity on tax avoidance. Sales growth weakens the negative effect of earnings management on tax avoidance